2020
DOI: 10.1016/j.clon.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Access Palliative Radiotherapy Programmes

Abstract: One of the greatest successes of radiotherapy has been its ability to palliate symptoms from advanced and metastatic cancers. Unfortunately, patients face barriers to accessing care and the demand for treatment is rising. Rapid access palliative radiotherapy programmes were created in response to these concerns, and over time they have proliferated and succeeded internationally. This narrative review provides an overview of programmes that have published their experiences, and discusses how they have improved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…Initially established in Canada in the 1990s in response to increasingly unacceptable waiting times, these clinics were intended to expedite treatment, ideally employing single fractions on the day of attendance, thereby sparing patients with a limited lifespan from multiple visits to the department. 7 The concept was gradually adopted elsewhere, including ANZ. 7,8 However, a recent survey on the status of RAPRT clinics in ANZ found that this model has not been widely embraced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially established in Canada in the 1990s in response to increasingly unacceptable waiting times, these clinics were intended to expedite treatment, ideally employing single fractions on the day of attendance, thereby sparing patients with a limited lifespan from multiple visits to the department. 7 The concept was gradually adopted elsewhere, including ANZ. 7,8 However, a recent survey on the status of RAPRT clinics in ANZ found that this model has not been widely embraced.…”
Section: Introductionmentioning
confidence: 99%
“…7 The concept was gradually adopted elsewhere, including ANZ. 7,8 However, a recent survey on the status of RAPRT clinics in ANZ found that this model has not been widely embraced. It found that only three of ANZ's 110 RT departments (2.7%) currently have a RAPRT clinic while five others (4.5%) have closed theirs, leaving 93% of centres which have never had one.…”
Section: Introductionmentioning
confidence: 99%
“…Nearly one in two Canadians will develop cancer in their lifetime 10 . It is documented that approximately 50% of all cancer patients will require RT 11 , with close to 50% requiring pRT 12 . This creates a significant burden on the RT programs in Ontario, which is projected to continue to grow over time.…”
Section: Scope Of Problemmentioning
confidence: 99%
“…2 With the growing incidence and mortality of breast cancer globally, more women will stand to require palliative radiotherapy. International programmes have been developed to provide rapid access to palliative care, 3 and efforts need to be streamlined in low-income…”
Section: Descriptionmentioning
confidence: 99%